LAND CAPABILITY EVALUATION FOR ECOTOURISM DEVELOPMENT IN ILAM PROVINCE, A GIS APPROACH - Ahmadi, Mehdi; Asgari, Shamsollah; Ghanavati, Ezatollah (Boletim de Ciências Geodésicas, 2015)
As one of the most wealth-generating industries in the world, tourism has been the center of attention by many governments worldwide. Depending on the purpose of tourism, it has been classified into different types, one of which is ecotourism. Given that ecotourism currently accounts for a small part of the whole, however, it has a rapid growth rate. The present study aims at zoning suitable areas in Ilam, a province in western Iran, for ecotourism development purposes. Accordingly, the digital maps of elevation, slope, land cover/land use, mineral springs, and water resources were prepared, at first. Afterwards, the suitable and unsuitable areas were segregated by Boolean functions. Overlaying the map layers by GIS software, the suitable areas were identified. The obtained results revealed that the top attractions are mainly distributed from the northern and central province to the southeastern parts where climatic condition is favorable, and rich in natural land cover and water resources. Moreover, the southern and western parts were evaluated poor in term of eco-tourist attractions.